Modeling Potential Autophagy Pathways in COVID-19 and Sarcoidosis. Issue 10 (October 2020) - Calender, Alain; Israel-Biet, Dominique; Valeyre, Dominique; Pacheco, Yves
Abstract : Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and mainly affects the lungs. Sarcoidosis is an autoinflammatory disease characterized by the diffusion of granulomas in the lungs and other organs. Here, we discuss how the two diseases might involve some common mechanistic cellular pathways around the regulation of autophagy.